EVALUASI PROGRAM KELUARGA HARAPAN (PKH) DALAM MENGATASI KEMISKINAN DI DESA BATU KE’DE KECAMATAN MASALLE KABUPATEN ENREKANG - Taufiq, Muh; Burhanuddin, Burhanuddin; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine how the evaluation of the Family Hope Program (PKH) in overcoming poverty in Batu Ke'de Village, Masalle District, Enrekang Regency. The type of research used is descriptive qualitative research with phenomenological research type. The results of the research conducted showed that the Evaluation of the Family Hope Program (PKH) in Batu Ke'de Village, Masalle District, Enrekang Regency saw from aspect 1.) the input in its implementation had been supportive, both in terms of supporting resources, facilities and infrastructure and sufficient human resources. 2.) The implementation process starts from the initial meeting, verification of commitment and assistance is in accordance with PKH implementation guidelines. 3.) Outputs in the implementation of PKH provide the expected results such as utilization in the fields of education and health. 4.) the resulting outcome is that the community is greatly assisted in the field of education in supporting the needs of school children